Concordance of the vestibular bone thickness at the level of point a between teleradiography and cone beam computed tomography. - Carolina Vergara; Sebastián Espinoza; Paulina González; Camila Martens; Patricio Rojas; Pedro Córdova (Universidad de Concepción., 2023)
Objective: The aim of this study was to determine the concordance of the vestibular bone thickness measured at the level of point A between Teleradiography and Cone Beam Computed Tomography (CBCT). Materials and Methods: This study consisted of a cross-sectional analytical design of concordance that evaluated the teleradiographies and CBCTs of 32 patients. The measurements were performed by three evaluators, specialists in orthodontics. Two of them measured the CBCTs and one evaluated the teleradiographs. The concordance of both tests was determined using the Concordance Correlation Coefficient. Results: When evaluating the value of the vestibular bone thickness at the level of point A between the CBCT and the teleradiography, it was observed that the mean value of the absolute difference between the two was 0.95±0.74, 95%CI [0.68-1.22], being statistically significant (p=0.0027). When the concordance between both tests was analyzed, it was observed that it was poor (CCC=0.204 95%CI [0.014-0.394]), although statistically significant (p<0.00001). Conclusions: It was possible to conclude that there is no concordance in the measurement of the vestibular bone thickness at the level of Point A between the Teleradiography and the CBCT.